COMPARISON OF SRI-KEHATI INDEX RETURNS & LQ45 INDEX - Darmawan, Dicky; Kwanto, Ivan (Dynamic Management Journal, 2024)
This writing aims to uncover and assess the disparity in returns between the LQ45 index and the Sri-Kehati index. The writing will employ the Independent Sample t-test methodology and will utilize SPSS software for conducting data analysis. The research sample consists of monthly index returns and shares included in the LQ45 and Sri-Kehati index categories in the 2018-2022 period. The study results indicate an absence of a noteworthy distinction in returns between the LQ45 index and the Sri-Kehati index.